A User Experience and Usability Test on Creating Games Specified as Graph Grammars - Silva, Júlia Veiga da; Silva Junior, Braz Araujo da; Foss, Luciana; Cavalheiro, Simone André da Costa (Anais do Workshop sobre Educação em Computação (WEI), 2023)
GrameStation is a game engine based on Graph Grammar that allows creating and playing games modeled with this language. Graph Grammar is an intuitive formal language, but people who do not have previous experience with it may have difficulty understanding/specifying games in this way. Therefore, we propose an experiment to analyze the support provided by GrameStation during the creation of games modeled as Graph Grammars in order to facilitate this task. We analyzed three groups of people with different levels of knowledge about Graph Grammar. They created a game following provided instructions and answered a questionnaire. It is concluded that GrameStation is suitable for those who have experience with it, but presents gaps for people without experience. These results will guide the implementation of pedagogical agents in the tool.